1996
DOI: 10.1046/j.1365-2362.1996.460602.x
|View full text |Cite
|
Sign up to set email alerts
|

To determine the effects of ultraviolet light, natural light and ionizing radiation on pyridinium cross‐links in bone and urine using high‐performance liquid chromatography

Abstract: The aims of the study were to characterize the denaturation of urinary free and conjugated pyridinoline (Pyr) and deoxypyridinoline (Dpyr) on exposure to ultraviolet (UV) and natural light at different pH levels and to study the effects of X- and gamma-irradiation on Pyr and Dpyr in urine and in the mineralized and non-mineralized compartments of human bone. Urine samples from six normal subjects, adjusted to pH 3.0, 7.0 and 9.0 were exposed to UV light for up to 3 days. Urine collections (2 mL and 24 h) from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 26 publications
(37 reference statements)
2
9
0
Order By: Relevance
“…We have previously observed increases in the amide I peak with dehydration and increasing age and have attributed them to broadening of the resonance profile for the amide   * transition caused by changes in the intrafibrallar environment of the collagen molecules [49,50]. Here, we believe that the increase is due to increased collagen cross-linking induced by the radiation damage, as similarly reported for gamma radiation studies [15][16][17]. Finally, we note that at a dose of 630 kGy, the spectral features were broadened to an extent such that the individual peaks could not be observed.…”
Section: Crack-growth Observationssupporting
confidence: 79%
See 2 more Smart Citations
“…We have previously observed increases in the amide I peak with dehydration and increasing age and have attributed them to broadening of the resonance profile for the amide   * transition caused by changes in the intrafibrallar environment of the collagen molecules [49,50]. Here, we believe that the increase is due to increased collagen cross-linking induced by the radiation damage, as similarly reported for gamma radiation studies [15][16][17]. Finally, we note that at a dose of 630 kGy, the spectral features were broadened to an extent such that the individual peaks could not be observed.…”
Section: Crack-growth Observationssupporting
confidence: 79%
“…It is well documented that this can be severely affected by radiation. In particular, the majority of damage from gamma radiation is induced in bone by the radiolysis of water molecules which generate free radicals which in turn target bonds within the collagen structure [62,63], resulting in cross-linking reactions in the collagen molecules [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tissue damage caused by gamma radiation occurs through two mechanisms Colwell et al 1996;Dziedzic-Goclawska et al 2005;Hamer et al 1999). In the dry state, splitting of polypeptide chains occurs under the direct influence of gamma rays (Dziedzic- Goclawska et al 2005).…”
Section: Mechanism Of Tissue Damage By Gamma Radiationmentioning
confidence: 99%
“…The studies on detrimental effects of gamma sterilization on elastic and plastic properties of the bone have demonstrated that decreased cross-linking of the collagen (Cheung et al, 1990;Bailey, 1967;Salehpour et al, 1995;Akkus et al, 2005;Ward, 1990;Wang et al, 2001;Colwell et al, 1996) significantly affects the mechanical properties of the bone within the plastic region (Akkus et al, 2005;Currey et al, 1997;Hamer et al, 1996) and results in ductility reduction, while elastic properties remain almost unaffected (Akkus et al, 2005;Currey et al, 1997). For instance, the reduction of the post-yield strength (by 70-87%) and decrease of the fatigue strength (by 87%) of the femoral cortical bone exposed to 36.4 kGy have been reported (Akkus et al, 2005;Currey et al, 1997).…”
Section: Introductionmentioning
confidence: 99%